2010
DOI: 10.1002/evan.20267
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of cattle: How aurochs became cattle and colonized the world

Abstract: Since their domestication in the Neolithic, cattle have belonged to our cultural heritage. The reconstruction of their history is an active field of research1 that contributes to our understanding of human history. Archeological data are now supplemented by analyses of modern and ancient samples of cattle with DNA markers of maternal, paternal, or autosomal inheritance. The most recent genetic data suggest that maternal lineages of taurine cattle originated in the Fertile Crescent with a possible contribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
164
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 206 publications
(184 citation statements)
references
References 78 publications
6
164
0
6
Order By: Relevance
“…The finding of two separate domestication events, one for taurine (Bos taurus) and one for zebu (Bos indicus) cattle [4,5], corresponded with the archaeological record. The exclusive presence of taurine mtDNA in African zebu [4] indicated that zebu was introduced into Africa by male introgression alone and demonstrated the unique contribution of mtDNA analysis to the reconstruction of agricultural history.…”
Section: Introductionsupporting
confidence: 57%
“…The finding of two separate domestication events, one for taurine (Bos taurus) and one for zebu (Bos indicus) cattle [4,5], corresponded with the archaeological record. The exclusive presence of taurine mtDNA in African zebu [4] indicated that zebu was introduced into Africa by male introgression alone and demonstrated the unique contribution of mtDNA analysis to the reconstruction of agricultural history.…”
Section: Introductionsupporting
confidence: 57%
“…Although intensive artificial selection has shaped cattle during recent centuries, domesticated cattle are derived from large-bodied, sexuallydimorphic aurochs (Bos primigenius) [42][43]. Among beef cattle, several small studies have revealed sex-biased milk production that favors sons [44], favors daughters [45], or no sex-biases [46].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, since their domestication, they have played a major role in human culture by participating in fighting games, racing and religious ceremonies. Because of the animal's size, the husbandry of cattle requires a more organized management than the keeping of other livestock, which may well have made a major contribution to the growing complexity and stratification of early agricultural societies [1]. As with other domestic species, their dispersal over different continents and adaptation to various environments has led to the development of many types of cattle [1].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the animal's size, the husbandry of cattle requires a more organized management than the keeping of other livestock, which may well have made a major contribution to the growing complexity and stratification of early agricultural societies [1]. As with other domestic species, their dispersal over different continents and adaptation to various environments has led to the development of many types of cattle [1]. This wide variety of characteristics evolved over thousands of years, but was accentuated by the development of well defined, specialized and genetically isolated breeds during the last centuries.…”
Section: Introductionmentioning
confidence: 99%